Storytelling and Magic: Meaning Making in Immigration Policing - Ana Aliverti (International Journal for Crime, Justice and Social Democracy, 2023)
This article explores the place of storytelling and magic in immigration policing in the United Kingdom. ‘Immigration stories’ are important for grasping the role of narratives in migration policing. While aimed at rendering a complex social world legible, this form of knowledge reveals its limitations. Rather than producing a cognitive template to make sense of a boundless world, immigration enforcement practices show illegibility as a hallmark of the state. The work of immigration officers is dominated by hazardous and arbitrary practices and rules⸻which I call ‘immigration magic’⸻which often leave them devoid of power and control. As an exercise in southernising border criminology, I interrogate the received division of labour in theorising the state in the south and north, on the one hand, and state and society on the other. In doing so, I seek to lay this northern policing bureaucracy open to underexplored dimensions and angles, as frontline staff are tasked with re-spatialising state power.